Unveiling the Speaking Strategies of High-Achieving EFL Students: A Case Study on the Implementation of 'Aqeel & Chung' Framework - Soviyah; Isna Rodiana Binti Munawaroh (Program Studi Tadris Bahasa Inggris, Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2026)
High-achieving EFL students consistently outperform peers in oral assessments, yet the integrated strategic mechanisms underlying their success remain underexplored in the literature. This study aims to identify, describe, and analyze the multidimensional public speaking strategies employed by top-performing students in an Advanced Speaking course. A qualitative case study design was employed. Four students from the English Education Department of a private university in Yogyakarta, Indonesia, were selected through purposive sampling based on consistently high oral examination scores. Data were collected via semi-structured interviews and observation of recorded presentations, and then analyzed through thematic coding cross-referenced with the Aqeel & Chung (2024) framework. Findings reveal that high-achieving students operate through a coordinated, three-dimensional strategy system: (1) Structure & Preparation (scripting, outlining, strategic topic selection, and pre-dawn memorization); (2) Internal Regulation via the Three Cs (cultivating awareness, collecting thoughts through strategic silent pausing, and calming nerves); and (3) Vocal & Non-Verbal Delivery (pitch modulation, posture, eye contact, and audience redirection). Public speaking success among high-achieving EFL students is not incidental but emerges from deliberate, systemic, and self-regulated practices spanning pre-, during-, and post-performance phases. These findings have direct implications for redesigning speaking pedagogy to incorporate metacognitive and self-regulatory training alongside conventional rhetorical instruction.